A view Plan Sheet Pile: Design Chart for Cantilever Retaining Wall Construction for Active and Passive Earth Pressure in Baghdad Soil - Ali A Mohammed (Institute of Advanced Engineering and Science, 2014)
As society begins to demand greater and more efficient use of underground space, deep excavations are being carried out to meet the surging need for infrastructure in big cities. During excavation, an in situ wall system is often constructed to provide stability and to minimize movements of the adjacent ground. The choice of an appropriate retaining system depends on certain factors such as subsoil characteristics, groundwater condition, and building protection considerations. For some circumstances, steel sheet piling typically provides the most usual solution for the conditions encountered in the field. In order to ensure successful excavation work, the behaviors of the wall must be considered during the design phase. In this paper, the design of cantilever sheet pile walls involves the evaluation of loads imposed by soil, water, and surcharging was conducted using specialized computer program. The effect of variation in height, loading, and soil properties on the design was investigated. This paper is intended to enable the pile selection and penetration to be quickly determined for the certain construction cases of cantilever sheet pile in Baghdad soil. Finally, some simple guidelines to installation method and to prevent failures related to geotechnical works of sheet pile are presented.